2013
DOI: 10.1097/nnr.0b013e31826901d5
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study

Abstract: Adequate amount of fluid intake, participants' characteristics, and components of a fluid regimen are major cautions in interpreting the preliminary results. Fluid intake could be the least harmful and the cheapest method to reduce susceptibility for bacteriuria. Combining behavioral approaches such as improving access to fluid or scheduled toileting may be beneficial in reducing the occurrence of bacteriuria in incontinent elders in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…As detailed in Table 1 and Appendix Table 2, 7 studies 22, 24, 26, 31, 32, 35, 36 involved single interventions and 12 studies 15, 20, 21, 23, 25, 2730, 33, 34, 37, 38 included multiple interventions. Interventions to impact catheter use and care were evaluated in 13 studies, including appropriateness of use, 21, 25, 29, 30 improving catheter maintenance care, 15, 20, 29, 30 securement, 15, 29,30, 32 prompting removal of unnecessary catheters, 21, 25, 29, 30 improving incontinence care, 15, 21, 23, 25 bladder scanners, 37, 38 catheter changes, 35 and comparing alternatives (condom catheter or intermittent straight catheter) to use of an indwelling catheter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As detailed in Table 1 and Appendix Table 2, 7 studies 22, 24, 26, 31, 32, 35, 36 involved single interventions and 12 studies 15, 20, 21, 23, 25, 2730, 33, 34, 37, 38 included multiple interventions. Interventions to impact catheter use and care were evaluated in 13 studies, including appropriateness of use, 21, 25, 29, 30 improving catheter maintenance care, 15, 20, 29, 30 securement, 15, 29,30, 32 prompting removal of unnecessary catheters, 21, 25, 29, 30 improving incontinence care, 15, 21, 23, 25 bladder scanners, 37, 38 catheter changes, 35 and comparing alternatives (condom catheter or intermittent straight catheter) to use of an indwelling catheter.…”
Section: Resultsmentioning
confidence: 99%
“…The nineteen studies (Table 2) reported 12 UTI outcomes, 15, 20, 21, 23, 2531, 33 9 CAUTI outcomes, 15, 22, 32, 34, 35, 38 4 bacteriuria outcomes, 24, 36, 38 and 5 catheter use outcomes. 21, 29, 30, 37, 38 Five studies showed CAUTI reduction 15, 22, 32, 34, 35 (1 significantly 34 ); nine studies showed UTI reduction 13, 18, 19, 21, 23–25, 27, 28, 31 (none significantly); 2 studies showed bacteriuria reduction (none significantly).…”
Section: Resultsmentioning
confidence: 99%
“…As UTI is the most common infection in hospitals or aged care centres, dwellers with reduced functional status residing in these facilities are more vulnerable to have this infection 5 . There is a higher incidence of complicated UTI in this group of patients.…”
Section: Uti In the Hospital And Aged Care Settingsmentioning
confidence: 99%
“…The management of patients with UTI is challenging, not only from a medical perspective but also from their psychosocial aspects. This group of patients need significant mental support while they are treated in the hospital settings [1][2][3][4][5] . Some of these subjects may live in the aged care facilities as well.…”
Section: Introductionmentioning
confidence: 99%
“…The main objectives are the total operating expenses in the supply chain and some cost indicators derived from those. The suggested solving methods are Lagrangian relaxation-based method [1], genetic algorithms [2,3,4,5], game theory methods [6], heuristic methods [7,8,9,10], decision-making methods [11,12,13], fuzzy optimization [14], ant colony algorithm [15], particle swarm optimization [16], modified fruit fly optimization [17], other linear and non-linear techniques [18,19,20,21].…”
Section: Literature Reviewmentioning
confidence: 99%